Mitochondrial Function In Vivo Evaluated by NADH Fluorescence - Mayevsky, Avraham (Springer International Publishing : Imprint: Springer, 2015)
This book covers both the technological development and biomedical applications of NADH fluorescence. Topics covered include perspectives on the history of monitoring NADH fluorescence, the relationship between mitochondrial function and other functions at the tissue level, responses of NADH to physiological and pathophysiological conditions, monitoring of NADH in the human brain and other organs, and metabolism. It also includes an in-depth look at flavoprotein (Fp) fluorescence and NADH in relation to redox state. This is an ideal book for biomedical engineers, researchers, and graduate students interested in learning the biomedical applications of NADH fluorescence. This book also: Covers multisite monitoring of NADH, as well as multiparametric responses of NADH to physiological and pathophysiological conditions, and monitoring of various organs in various animal models Describes the relationship between brain activation (i.e. epileptic activity and cortical spreading depression) and NADH redox state Presents the effects of hypoxia, hyperbaric hyperoxia, and ischemia on brain NADH fluorescence and other tissue physiological parameters    About the Author Avraham Mayevsky, Ph.D. is a Professor Emeritus in the Faculty of Life Sciences and the Brain Research Center at Bar Ilan University, Israel. He has published  more than two hundred papers in the field of mitochondrial function and tissue physiology in vivo under pathophysiological conditions.